Integration of Religious Knowledge with Science and Technology in Islamic Education - Ali Wafa (Penerbit Hellow Pustaka, 2023)
Islamic education plays a major role in shaping the personality of individual Muslims and keeping abreast of the development of science and technology in the modern era. The integration of science and technology is an important need to achieve the goals of Islamic education that are relevant to the times. However, the application of science and technology in the Islamic Religious Education (PAI) curriculum did not run smoothly. Limited facilities and infrastructure in Islamic educational institutions, especially those with financial limitations, is one of the obstacles. This includes the availability of hardware, internet access, and training for teachers in using technology. This obstacle can hinder the development of a curriculum that is integrated with science and technology. In addition, concerns related to the negative impacts of technology, such as misuse of information, loss of social interaction, and influence on religious values, are also of concern. Therefore, a deep understanding of how to manage sai integration. The purpose of this study is to analyze the impact of these problems on the effectiveness of integrating science and technology in the PAI curriculum. The research method used is a literature review with a qualitative approach, collecting data from literature that discusses Islamic philosophy, thought, and civilization The findings from this study can provide guidance for improvement and improvement in overcoming the obstacles faced, so that Islamic Education can remain relevant and effective in the technological era.